New insights on the trophic ecology of bathyal communities from the methane seep area off Concepción, Chile (~36° S). (13th July 2013) - Zapata‐Hernández, Germán; Sellanes, Javier; Thurber, Andrew R.; Levin, Lisa A.; Chazalon, Frédéric; Linke, Peter
Abstract Studies of the trophic structure in methane‐seep habitats provide insight into the ecological function of deep‐sea ecosystems. Methane seep biota on the Chilean margin likely represent a novel biogeographic province; however, little is known about the ecology of the seep fauna and particularly their trophic support. The present study, using natural abundance stable isotopes, reveals a complex trophic structure among heterotrophic consumers, with four trophic levels supported by a diversity of food sources at a methane seep area off Concepción, Chile (~36° S). Although methanotrophy, thiotrophy and phototrophy are all identified as carbon fixation mechanisms fueling the food web within this area, most of the analysed species (87.5%) incorporate carbon derived from photosynthesis and a smaller number (12%) use carbon derived from chemosynthesis. Methane‐derived carbon (MDC) incorporation was documented in 22 taxa, including sipunculids, gastropods, polychaetes and echinoderms. In addition, wide trophic niches were detected in suspension‐feeding and deposit‐feeding taxa, possibly associated with the use of organic matter in different stages of degradation (e.g. from fresh to refractory). Estimates of Bayesian standard ellipses area (SEAB) reveal different isotopic niche breadth in the predator fishes, the Patagonian toothfish Dissostichus eleginoides and the combtooth dogfish Centroscyllium nigrum, suggesting generalist versus specialist feeding behaviors, respectively. Top predators in the ecosystem were the Patagonian toothfish D. eleginoides and the dusky cat shark, Bythaelurus canescens. The blue hake Antimora rostrata also provides a trophic link between the benthic and pelagic systems, with a diet based primarily on pelagic‐derived carrion. These findings can inform accurate ecosystem models, which are critical for effective management and conservation of methane seep and adjacent deep‐sea habitats in the Southeastern Pacific.